Testing the Effectiveness of Various Management Fertilizers on The Growth of Cashet (Anacardium Occidentale L.): Uji Efektivitas Berbagai Macam Pupuk Kandang Terhadap Pertumbuhan Bibit Tanaman Mete (Anacardium Occidentale L.) - Susniati Susniati; Badaria Badaria (JURNAL AGRIYAN: JURNAL AGROTEKNOLOGI UNIDAYAN, 2021)
Currently, the potential of cashew plantations in Southeast Sulawesi is quite large with the availability of potential land. It's just that the farmers have not been able to take full advantage of this potential so that the quality of production continues to decline. One of the efforts to increase cashew production is to require replanting with new seeds. The purpose of this study was to test the effectiveness of various uses of manure on the growth of cashew (Anacardium occidentale L.) seedlings. This research was conducted in Bonegunu Village, Bonegunu District, North Buton Regency from November 2020 to January 2021. The experimental design used was a randomized block design with a one-factor pattern consisting of 5 levels of treatment, namely: P0 = No Fertilizer 0 g/polybag, P1 = Chicken Manure 75 g/polybag, P2 = Cow Manure 75g/polybag, P3 = Goat Manure 75g/polybag, and P4 = Pig Manure 75g/polybag. If the results show a real effect, it will be continued with the honest real difference test (BNJ) at the 5% level. The responses observed were plant height (cm), number of leaves (strands), and stem diameter (cm). Based on the results of the study showed that the use of manure had a significant effect on plant height and stem diameter of cashew plants. Keywords: Cashew Plant (Anacardium occidentale L.), Chicken Manure, Cow Manure, Goat Manure, and Pig Manure.